Effect of End Anchorage in External CFRP Confinement on Shear Damaged RC Beams. (2015) - Frederick, Franklin F.R; Sharma, U.K.; Gupta, V.K.
Abstract: In recent days many structures are strengthened or restored to make use of the existing structure to the current needs. Upgrading a structure by restoration and strengthening eliminates the need of devastating and reconstruction also saves energy. In repair and retrofitting of a structural elements or a structure, appropriate techniques has to be choose according to the damage level or the requirement. Epoxy or any polymer injection is a kind of method to repair the cracked region. Fiber reinforced polymer (FRP) wrapping is a kind of external strengthening techniques being in practice to retrofit a reinforced concrete (RC) structure without increasing the dead load. In this study the effectiveness of externally bonded carbon-fiber-reinforced polymer (EB-CFRP) system with end anchorage on retrofitting of damaged RC beams has been examined. To represent a severe damage condition, control beams are tested to failure, retrofitted, and then retested to failure for a second time. The test results demonstrated that retrofitting of severely damaged RC T-beams with EB-CFRP composite with proper end anchorage can fully restore the original shear capacity of the beams without increasing the dimension of the structural member. Also this end anchorage system significantly restricts the delamination of FRP during severe loading than EB-CFRP method.